Programma: 20 oktober White Lion; 25 oktober 10.000 Maniacs; 26 oktober Henry Rollins; 29 oktober Lee Clayton
Programma: 20 oktober White Lion; 25 oktober 10.000 Maniacs; 26 oktober Henry Rollins; 29 oktober Lee Clayton.